Humboldt's gift - Bellow, Saul (Penguin classics., 2008)
Charlie Citrine, suffering from steadily worsening troubles with women, career, and life in general, receives unexpected aid and comfort in the form of a belated bequest from his onetime friend and mentor, the poet Von Humboldt Fleisher.